Strategic supplementation of sanguinarine in a soybean meal free diet for grass carp (Ctenopharyngodon idella) significantly enhances growth performance by promoting liver and intestinal health and optimizing bile acid metabolism - Yuhua Yue; Yong Shi; Meilin Zhang; Shanshan Shi; Guanping Liu; Hairong Shi; Yi Hu; Lei Zhong (Aquaculture Reports)
This study was undertaken to reduce reliance on imported soybeans, enhance aquaculture industry resilience, and seek functional soybean meal substitutes. Seven hundred fifty juvenile grass carp (Ctenopharyngodon idella) (initial weight: 24.00 ± 0.00 g) were assigned to five diets—soybean meal (SM), cottonseed meal (CM), cottonseed protein concentrate (CPC), and CM with 375 or 825 μg/kg (CMS1 or CMS2) sanguinarine—and, after eight weeks, evaluated for growth, liver and intestinal health, and bile acid metabolism. The results demonstrated that the CMS1 or CMS2 group significantly increased WGR and SGR, reduced FCR, enhanced serum and bile biochemical indices compared with CM group. Besides, histopathological examination of the CM group revealed hepatocellular damage, increased lipid droplet accumulation, elevated glycogen deposition, and more severe fibrosis, along with degeneration of gallbladder columnar epithelium; these lesions were markedly attenuated in the CMS1 and CMS2 groups. In the CM group, intestinal villi and microvilli were disrupted, goblet cell counts declined, and macrophage infiltration alongside widened tight junctions was evident; CMS1 and CMS2 groups markedly restored mucosal architecture to levels comparable with the SM and CPC groups. Finally, the CM group exhibited significant upregulation of lipogenic genes (PPAR-γ, SREBP1, FAS, ACC1, SCD and DGAT), alongside moderate increases in lipolytic genes (ATGL, HSL, LXR, PPAR-α, CPT, and APOE) relative to SM, CMS1, and CMS2 groups. Dietary sanguinarine supplementation markedly enhanced bile acid metabolism, as demonstrated by the upregulation of ABCC2, ABCB11b, CYP7A1, CYP7b1, FGF19, TGR5, SLC10A2 and CCK, together with the concomitant downregulation of SHP. Our findings demonstrate that supplementation of sanguinarine in cottonseed meal diets ameliorates hepatic lipid accumulation, bile acid dysregulation, and tissue damage by suppressing the LXR–PPAR–SREBP1 lipogenic pathway and activating the FXR–SHP/FGF19–CYP7A1 regulatory axis, ultimately enhancing liver and intestinal health and promoting growth performance in grass carp.